PENGARUH PENDEKATAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA KELAS X SMA NEGERI 1 SUTERA - Sefrinal Sefrinal (STKIP Pesisir Selatan, 2019)
This research was aimed at finding out (1) creative thinking, (2) creative thinking skills of students based on highand low knowledge, and (3) the interaction between of problem based learningwith the grade of primary abilityin influencing the creative thinking skills. This research is a quasi-experimental research. Sample of this research is students at X Sains 2 SMAN 1 Sutera and students at X Sains 3 SMAN 1 Sutera. The accumulation of data using test and the analysis of data by statistical. The results showed that (1) creative thinking comprehension skills of the students who were taught by using problem based learning had high score than the students whose where taught by using conventional model 2) creative thinking comprehension skills of the students whose high primary ability that were taught by using problem based learning had same score with the students who were taught by using conventional model 3) creative thinking comprehension skills of the students whose low primary ability that were taught by using problem based learning had high score than the students who were taught by using conventional model 4) whose were no interaction among the use of problem based learning and the grade of primary abilityin influencing the creative thinking comprehention skills.